Antiviral activity of merimepodib against foot and mouth disease virus in vitro and in vivo. (October 2019) - Li, Shi-fang; Gong, Mei-jiao; Shao, Jun-jun; Sun, Yue-feng; Zhang, Yong-guang; Chang, Hui-yun
Highlights: Merimepodib shows antiviral activity against FMDV in vitro, including two different serotypes of FMDV. The antiviral effect of merimepodib occurred in the early phases of FMDV replication. The antiviral effect of merimepodib could be attenuated by guanosine supplementation. In vivo activity of merimepodib was confirmed in a mouse model of infection. Abstract: Foot and mouth disease virus (FMDV), a member of family Picornaviridae, belongs to the genus Aphthovirus, which causes foot and mouth disease (FMD), a highly transmissible disease that affects cloven-hoof animals. In spite of the fact that efficient vaccines are available, effective antiviral molecules for FMD are needed to reduce viral infection during early stages of infection. In this study, merimepodib was found to efficiently inhibit FMDV replication in a dose-dependent manner. The 50% inhibitory concentration (IC50 ) of merimepodib antiviral activity against two distinct FMDV strains (O/MYA98/BY/2010 and A/GD/MM/CHA/2013) was estimated to be 7.859 and 2.876 μM, respectively, while the 50% cytotoxic concentration (CC50 ) of merimepodib was found to be 47.74 μM. Furthermore, treatment with 30 μg merimepodib efficiently prolonged the survival time of suckling mice infected with FMDV. Taken together, these results suggested that merimepodib has the potential to be a novel antiviral agent against FMDV.